2014
DOI: 10.1063/1.4871284
|View full text |Cite
|
Sign up to set email alerts
|

Strain-driven fractional spontaneous exchange bias in ferromagnetic/antiferromagnetic thin films with composition-graded ferromagnetic layer

Abstract: We experimentally demonstrate that the stress-induced magnetic anisotropy in composition-graded ferromagnetic NiFeTa layers can be employed to trigger exchange bias in NiFeTa/IrMn bilayers without using any deposition field or field cooling procedure. In particular, we found that the NiFeTa/IrMn bilayers exhibit double-shifted loops being composed of both negative and positive exchange biases when the deposition angle is low. As the deposition angle is increased, the magnetization curves change into a single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It can also be recalled that the offset of the hysteresis loops (anomalous shift) in Fig. 3 set without any field applied during the multilayer growth or any FC protocol applied posteriorly after the sample preparation may have its origin in this hardening of the FM layer, as it was observed in literature [63] where an exchange bias was set by only the stress-induced effect in a NiFeTa/IrMn system with a laterally composition-graded 150 nm ticker NiFeTa layer. From the magnetic behavior of the top Py sublayer observed in Fig.…”
Section: B Structural Investigationmentioning
confidence: 54%
“…It can also be recalled that the offset of the hysteresis loops (anomalous shift) in Fig. 3 set without any field applied during the multilayer growth or any FC protocol applied posteriorly after the sample preparation may have its origin in this hardening of the FM layer, as it was observed in literature [63] where an exchange bias was set by only the stress-induced effect in a NiFeTa/IrMn system with a laterally composition-graded 150 nm ticker NiFeTa layer. From the magnetic behavior of the top Py sublayer observed in Fig.…”
Section: B Structural Investigationmentioning
confidence: 54%
“…Furthermore, the presence of the microscopic unidirectional exchange anisotropy interaction at the FM/AFM interface is responsible for the exchange bias [41]. Phuoc et al [42,43] have found that the onset of dynamic magnetic anisotropy occurs at the AF thickness of 2 nm, lower than critical AF thickness for the onset of static magnetic anisotropy and exchange bias. Therefore, we believe that in our work the exchange bias is due mainly to the contribution of exchange coupling and anisotropy.…”
Section: Resultsmentioning
confidence: 97%